Health policy for sickle cell disease in Africa: experience from Tanzania on interventions to reduce under‐five mortality. Issue 2 (17th November 2014) - Makani, Julie; Soka, Deogratias; Rwezaula, Stella; Krag, Marlene; Mghamba, Janneth; Ramaiya, Kaushik; Cox, Sharon E.; Grosse, Scott D.
Abstract Tanzania has made considerable progress towards reducing childhood mortality, achieving a 57% decrease between 1980 and 2011. This epidemiological transition will cause a reduction in the contribution of infectious diseases to childhood mortality and increase in contribution from non‐communicable diseases (NCDs). Haemoglobinopathies are amongst the most common childhood NCDs, with sickle cell disease (SCD) being the commonest haemoglobinopathy in Africa. In Tanzania, 10 313 children with SCD under 5 years of age (U5) are estimated to die every year, contributing an estimated 7% of overall deaths in U5 children. Key policies that governments in Africa are able to implement would reduce mortality in SCD, focusing on newborn screening and comprehensive SCD care programmes. Such programmes would ensure that interventions such as prevention of infections using penicillin plus prompt diagnosis and treatment of complications are provided to all individuals with SCD.